The effectiveness of cognitive-behavioral therapy in improving symptoms of children with chronic tic disorder - Azarbuyeh, Mona; Bakhshipour Rodsari , Abbas; Mashhadi , Ali (Social Determinants of Health, 2021)
Background: The Chronic tic disorder is a single tic or several sudden tics that continue several times a day for more than a year and it can be simple or complex. ​​Children with tic disorder stigmatized and consider the judgment of others very much, which could impair their quality of life. The purpose of this study was to explore the effectiveness of cognitive-behavioral therapy (CBT) in improving the symptoms of children with chronic tic disorder. Method: This research was a single case type A-B-A with multiple baseline design and follow-up. The study population was 10–13-year-old boys with tic disorder who referred to Astan-e-Mehr Psychiatric Clinic in Mashhad in 2018-2019. Sampling was done through purposive sampling method in which three cases (one with simple and two with complex tic disrder) were selected using a clinical interview by a clinical psychologist. The subjects responded to the Global Tic Severity Scale in baseline situations, intervention sessions, and one month after the intervention. The CBT was performed in 14 sessions. Data analysis was performed using trend chart method and the effect size. Results: The results of each subject showed a significant difference between the intervention position and baseline for three subjects with paroxysmal nocturnal dyspnea (PND) 100% for subject number one, 78% for subject number two and 86% for subject number three. Also, in the follow-up situations, the performance of all subjects was maintained., Conclusion: the CBT could be effective in improving the symptoms of children with chronic tic disorder.